Deglycosylation of Excretory-Secretory Antigens of the Second-Stage Larvae of Toxocara cati Improves Its Efficacy in the Diagnosis of Human Toxocariasis - Ali Pouryousef; Bahador Sarkari; Amir Mootabi Alavi; Mostafa Omidian; Fattaneh Mikaeili (Journal of Tropical Medicine)
Background. Toxocariasis is an important zoonotic infection, especially in tropical areas. One of the significant challenges in the serodiagnosis of human toxocariasis is the cross-reaction of Toxocara antigens with other parasites due to their relatively similar glycan structures. Removing the glycan structure from Toxocara excretory-secretory (TES) antigens may increase the efficacy of these antigens in the diagnosis of toxocariasis. The current study aimed to assess the efficacy of deglycosylated Toxocara cati excretory-secretory (dTES) antigens for the serodiagnosis of human toxocariasis. Methods. Toxocara ES antigens were prepared from T. cati second-stage larvae and deglycosylated using sodium hydroxide (NaOH). The TES antigens, along with the dTES antigens, were used in an ELISA as well as a western blotting system for the detection of anti-Toxocara antibodies. Sera samples collected from 30 confirmed cases of toxocariasis, 30 patients with other diseases, and 30 healthy subjects were evaluated by both systems. Results. The sensitivity of TES and dTES ELISA for the diagnosis of human toxocariasis was 96.67% (95% CI = 82.78–99.92) and 93.33% (95% CI = 77.93–99.18), respectively, while the specificity of dTES (88.33%; 95% CI = 77.43–95.18) increased significantly compared to the TES (80.00%; 95% CI = 67.67–89.22). The sensitivity of both antigens was 100% (95% CI = 88.43–100) by the western blotting system. Moreover, the specificity of TES and dTES antigens was 95% (95% CI = 86.08–98.96) and 98.33% (95% CI = 91.06–99.96), respectively, when using the western blotting system. Conclusion. Results of the current study indicate that the chemical removal of the glycan epitopes of T. cati ES antigens significantly reduces cross-reactivity rates with other parasitic infections. Considering the findings of the present study, the dTES antigens seem to be suitable antigens for the serodiagnosis of human toxocariasis.